Ekologizacija literarne vede in ekokritika - Čeh Steger, Jožica (Slavistična revija, 2012)
Ecocriticism as a special discipline of literary criticism in the 1990s first took hold in the Anglo-American world and from there it spread to the countries of Continental Europe and Asia. After being initially limited to the study of images and genres of nature, its scope of research later broadened to include various theoretical concepts of nature, relationships between culture and nature, man and the environment, i.e., literature as a whole, and contributed significantly to the realization that man is defined not only by social relations, but to the same extent by natural environment. The article focuses on the development of ecocriticism, its subject areas, questions related to the ecological function of literature, and to individual elements of ecocritical analysis of a literary text.
Keywords: ecology; ekofeminizem; ekologija; ekološka kritika; književnosti; literarna ekologija; literarna teorija; literary theory